Long-Term Prognosis of Hyperferritinemia Induced by Intravenous Iron Therapy in Patients Undergoing Maintenance Hemodialysis: A 10-Year, Single-Center Study - Sayako Maeda; Ryo Konishi; Takuya Morinishi; Yoko Shimizu; Haruomi Nishio; Koji Takaori (International Journal of Nephrology)
Optimal ferritin level in hemodialysis patients between Japan and other countries is controversial. Long-term side effects of iron supplementation in these patients remain unclear. We aimed to elucidate whether past hyperferritinemia in hemodialysis patients was associated with high risk of death and cerebrovascular and cardiovascular diseases (CCVDs). This small retrospective cohort study included approximately 44 patients unintentionally supplemented with excessive intravenous iron. A significantly higher risk of CCVDs was observed in patients with initial serum ferritin levels ≥1000 ng/mL than in the remaining patients. High ferritin levels slowly decreased to <300 ng/mL in a median of 24.2 (10.5–46.5) months without treatment. However, compared with the remaining patients, only patients whose ferritin levels did not decrease to <300 ng/mL steadily had a significantly higher risk of all-cause death (hazard ratio, 9.6). Long-term hyperferritinemia due to intravenous iron therapy is a risk factor for death in maintenance hemodialysis patients. For a prolonged better prognosis, intravenous iron should be carefully administered so as to avoid hyperferritinemia in patients with hemodialysis.